Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1039/b911600c
|View full text |Cite
|
Sign up to set email alerts
|

Clathrate hydrates with hydrogen-bonding guests

Abstract: Clathrate hydrates (CHs) are inclusion compounds in which "tetrahedrally" bonded H(2)O forms a crystalline host lattice composed of a periodic array of cages. The structure is stabilized by guest particles which occupy the cages and interact with cage walls via van der Waals interactions. A host of atoms or small molecules can act as guests; here the focus is on guests that are capable of strong to intermediate H-bonding to water (small ethers, H(2)S, etc.) but nevertheless "choose" this hydrate crystal form i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
245
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(264 citation statements)
references
References 58 publications
19
245
0
Order By: Relevance
“…Pure ammonia clathrate hydrate synthesis cannot be done by simply cooling aqueous ammonia solutions, as a variety of stoichiometric hydrates of ammonia are known to form preferentially (2,11,18,19). Other ways of forming clathrate hydrates include vapor deposition of water at low temperatures to yield amorphous ice, followed by exposure of the ice to a pressure of guest gas and annealing (29), or vapor codeposition of water and the potential guest material at low temperatures, again, followed by annealing (23,30,31). It has been shown that below approximately 140 K ice surfaces are relatively inert unless strong hydrogen-bond donors or acceptors are present.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pure ammonia clathrate hydrate synthesis cannot be done by simply cooling aqueous ammonia solutions, as a variety of stoichiometric hydrates of ammonia are known to form preferentially (2,11,18,19). Other ways of forming clathrate hydrates include vapor deposition of water at low temperatures to yield amorphous ice, followed by exposure of the ice to a pressure of guest gas and annealing (29), or vapor codeposition of water and the potential guest material at low temperatures, again, followed by annealing (23,30,31). It has been shown that below approximately 140 K ice surfaces are relatively inert unless strong hydrogen-bond donors or acceptors are present.…”
Section: Resultsmentioning
confidence: 99%
“…Recent structural analysis and molecular simulations have shown that some guest molecules which form strong hydrogen bonds with the water framework of the clathrate hydrate lattice may nonetheless produce stable phases (20)(21)(22)(23). It is therefore reasonable to consider that ammonia has potential as a clathrate guest molecule.…”
mentioning
confidence: 99%
“…This implies that there is some hostguest interaction, and indeed, hydrogen-bonding is known to occur for a variety of guest molecules in clathrate hydrates, including small ethers. [31][32][33] To explore the possibility of strong radical-host interactions, we performed a DFT calculation on tetrahydrofuran-3-yl (the H isotopomer of 1) at the center of a single cage of 28 water molecules arranged to mimic the 5 12 .) The focus of the present paper is on the identification of guest radicals.…”
Section: Resultsmentioning
confidence: 99%
“…There have also been recent IR, Raman, and molecular dynamics ͑MD͒ studies of hydrates and evidence of hydrogen-bond formation with the guests has been observed. 16 Unlike ketone and ether guests studied previously, alcohols act as both hydrogen-donors and hydrogen-acceptors in hydrogen bonding with water and both types of bonds are considered and analyzed. The dynamics of the guest motions are studied and correlated with the effects of guest-water hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%